2015
DOI: 10.1111/bjd.13639
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe acne

Abstract: SummaryAcne is the most common skin disease, affecting up to 95% of adolescents. Severe episodes of acne can cause considerable physical and psychological scarring, and overexpression of transforming growth factor-b can lead to formation of hypertrophic scars and keloids. The severity of acne in adolescence is associated with a positive history of severe acne in first-degree relatives, especially the mother. In most cases acne is a chronic disease, and it is often a component of systemic diseases or syndromes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 85 publications
(98 reference statements)
1
54
0
3
Order By: Relevance
“…Furthermore, it has been suggested that some patients may experience depression while using oral isotretinoin, but studies have not shown a decisive relationship. 7,14,15 The development of bacterial resistance and ensuing recommendations from health authorities has limited the use of local and systematic antibiotics, favoring their use within the framework of combined therapy regimens. 16,17 Nevertheless, in 12% of cases, only one local or systematic antibiotic has been noted to be prescribed by European dermatologists, which contradicts the published recommendations and indicates that dermatologists should not use antibiotics alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that some patients may experience depression while using oral isotretinoin, but studies have not shown a decisive relationship. 7,14,15 The development of bacterial resistance and ensuing recommendations from health authorities has limited the use of local and systematic antibiotics, favoring their use within the framework of combined therapy regimens. 16,17 Nevertheless, in 12% of cases, only one local or systematic antibiotic has been noted to be prescribed by European dermatologists, which contradicts the published recommendations and indicates that dermatologists should not use antibiotics alone.…”
Section: Discussionmentioning
confidence: 99%
“…Bakteri tersebut ikut serta dalam patogenesis jerawat dengan menghasilkan lipase, yang memecahkan asam lemak bebas dari lipid kulit 5 . Asam lemak ini dapat menimbulkan radang jaringan dan ikut menyebabkan jerawat 6 . Populasi bakteri penyebab jerawat tersebut dapat diturunkan dengan memberikan suatu zat antibakteri seperti tetrasiklin, kloramfenikol dan amoksisilin 7 .…”
Section: Pendahuluanunclassified
“…Pada penggunaannya obat jerawat yang ada di pasaran memiliki efek samping yang lebih besar daripada obat jerawat yang berasal dari alam 13 , misalnya efek samping yang diakibatkan dari antibiotik yang digunakan pada produk anti jerawat yang ada di pasaran yaitu reaksi alergi yang diakibatkan oleh antibiotik dengan melibatkan sistem imun tubuh hospes. Selain itu efek samping yang ditimbulkan yaitu reaksi hipersensitifitas 6 , adanya ketergantungan obat yang terjadi karena interaksi suatu obat dengan organisme hidup 7 , ada suatu senyawa yaitu Isotretinoin yang digunakan untuk mengobati jerawat yang berat 13 , psoriasis dan kelainan kulit lainnya bisa menyebabkan cacat bawaan 14 . Yang paling sering terjadi adalah kelainan jantung, telinga yang kecil dan hidrosefalus (kepala yang besar) 15 .…”
Section: Pendahuluanunclassified
“…Adverse effects of isotretinoin are well defined being the major limiting factor for its usage. Next to mucocutanous changes, teratogenicity as well as psychiatric and endocrinological side effects have been reported [1].…”
Section: Introductionmentioning
confidence: 99%